61.4k views
2 votes
SOMEONE HELP ME PLS, I'M stuck on this one since yesterday!

Given: F = {(0, 1), (2, 4), (4, 6), (6, 8)} and G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}

(F . G) (2) =

1 Answer

5 votes

\bf \begin{cases} F = \{(0, 1), (\stackrel{x}{2}, \stackrel{y}{4}), (4, 6), (6, 8)\} & F(\stackrel{x}{2})=\stackrel{y}{4} \\\\\\ G = \{(\stackrel{x}{2}, \stackrel{y}{5}), (4, 7), (5, 8), (6, 9), (7, 5)\} \qquad & G(\stackrel{x}{2})=\stackrel{y}{5} \end{cases} \\\\\\ (F\cdot G)(2)\implies F(2)\cdot G(2)\implies 4\cdot 5\implies 20
User TFD
by
5.6k points